J. Basanavičius’ relations with USA editor A. Milukas - Gargasaitė, Dalia (Knygotyra, 1992)
In the article are brought to light the relations of famous scientist and folklore master J. Basanavičius with USA editor of Lithuanian origin, priest A. Milukas. By his efforts four books of J. Basanavičius were printed in USA – folklore compositions. They are still of great scientific value.